Comparison of Frequency of Pseudo-Exfoliation Syndrome in Patients Undergoing Cataract Surgery in Different Regional Hospitals of Pakistan - Hussain, Irshad; Rauf, Abdul; Ishtiaq, Omar; Islam, Qamar-ul-; Khan, Faisal Aziz; Ali, Shahzad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the frequency of Pseudo-Exfoliation Syndrome (PXS) in patients undergoing cataract surgery in different regional hospitals in Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Three Tertiary Care Hospitals of Karachi, Rawalakot and Skardu Pakistan, from Sep 2017 to May 2020. Methodology: Patients aged 45 years and more undergoing age-related cataract surgery were evaluated for Pseudo-Exfoliation Syndrome. Initially, each patient underwent a complete outpatient ophthalmological workup. Demographic details like age and gender were noted. All the patients were screened for hypertension and diabetes mellitus. In addition, patients were screened for pseudo-exfoliation syndrome. Congenital, developmental, secondary and traumatic cataracts were excluded. Results: A total of 1882 patients were included in the study. Pseudo-exfoliation was carried out in 249(13.23%) patients. In Hospital-A, 23(3.23%); in Hospital-B, 145(14.92%) and Hospital-C, 81(40.70%) of the patients had pseudo-exfoliation. The frequency of pseudo-exfoliation syndrome was significantly more in Hospital-C and then in Hospital-B and least in HospitalA (p<0.01). Conclusion: Pseudo-exfoliation syndrome was significantly more common in Skardu and then in Rawalakot and least in Malir, which in the same order have more latitude away from the equator, have less average annual temperature and are situated at higher altitudes.